The Digital Challenge - New perspectives for the Metamorfoze Programme - Schouten, Dennis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
2007 is an important year for the Metamorfoze programme. The budget has increased substantially, which allows the programme to be carried out on a much larger scale. Government archives are now included in the programme as well, and, last but not least, Metamorfoze is shifting towards digitization as a conversion method for mass-preservation projects instead of microfilming. This paper will give an overview of these new developments and plans for the future, but it will start with a short retrospective.